(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2023)
The husks or pods of peas are residues that are obtained once the seeds are removed from their envelope. This agro-industrial waste is rich in carbohydrates, proteins, vitamins, pigments and even phenolic compounds. In order to take advantage of this by-product, the object of the research was to study the influence of chemical treatments on the physical properties of the pea pod. Initially, the pea pod was treated with 0.5 % and 2% oily acid, with 2.5 % sodium bisulfite and an untreated control sample. Subsequently, the pods were analyzed by determining the color by colorimetry using the CieLab scale, hardness by texturometer, total chlorophyll content (TCh) and carotenoids (TCa) by visible spectrophotometry at 663 mm, 645 mm and 410 mm respectively. The pods treated with 0.5 % acetic acid presented the highest values of the parameter of b * of 19.17 and those treated with sodium bisulfite at 2.5 % presented significant differences (p less than or equal to 0.05) with respect to the other samples in the parameters of luminosity (L) and (b *). With respect to hardness the force required for the break was 28 to 32 N in a span of 16 to 18 seconds, indicating a correlation with moisture content, crude fiber and pectin content. The pigments contained in the pea pod can be used to enrich foods because it is a natural source of chlorophyll and carotenoids, providing a high nutritional value with attractive color and beneficial effects for human health.